Problems of Russian Theatrical Reception of Shakespeare in Criticism of Yuli Eichenwald - V. V. Serdechnaya; D. N. Zhatkin (Научный диалог)
The problem of this study lies in evaluating the methodological approach of Yuli Eichenwald (1872—1928) as a theatrical critic and theorist, specifically his writings on Shakespearean productions both in Russia and abroad. Known primarily as a literary critic, Eichenwald also wrote about theater, but his works in this area have been largely unexplored. The aim of this study is to shed light on Eichenwald's principles of theatrical criticism. The material used consists of little-known articles by Eichenwald on theater theory and Shakespearean productions from 1903 to 1927. The research employs hermeneutic and comparative methods. The findings reveal that Eichenwald demonstrates a literature-centric position in his articles on theater, according to which theater is merely an illustration of literary works. He increasingly uses productions as a pretext to discuss Shakespeare, often without mentioning the actors or directors. Eichenwald’s perception of theater as a mediator, as an auxiliary device between the play and the reader, leads to his rejection of the concept of directorial theater and the denial of the director as the author of the production. The authors conclude that Eichenwald’s theatrical criticism is a logical outcome of literature-centric judgments about theater, from Aristotle to Hegel, where theater is considered as part of literature.